2021
DOI: 10.4236/ss.2021.121001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Urinary Incontinence after Obstetric Vesicovaginal Fistula Closure in Guinea

Abstract: Introduction: Urinary incontinence after closure of vesicovaginal fistula is any involuntary loss of urine that a patient complains of. We aim to study the risk factors for urinary incontinence after closure of obstetric vesicovaginal fistula in Guinea in order to develop preventive measures to reduce its incidence. Materials and Methods: This was a retrospective, multiple center cohort of women operated on for obstetric vesicovaginal fistula during a 10-year period. Results: In 1770 vesicovaginal fistulas ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
3
5
1
Order By: Relevance
“…Collaboration with the teams of Kambou and Kaboré, who have extensive experience in the management of urogenital fistulas in Burkina Faso, could help improve our results [ 10 ]. The rate of residual urinary incontinence in the present study (12%) is similar to that reported in the literature [ 7 , 25 ]. Hillary et al .…”
Section: Discussionsupporting
confidence: 91%
“…Collaboration with the teams of Kambou and Kaboré, who have extensive experience in the management of urogenital fistulas in Burkina Faso, could help improve our results [ 10 ]. The rate of residual urinary incontinence in the present study (12%) is similar to that reported in the literature [ 7 , 25 ]. Hillary et al .…”
Section: Discussionsupporting
confidence: 91%
“…Although the successful obstetric VVF closure rate is greater than 90%, after successful obstetric VVF repair, patients complain of up to 55% UI [ 7 ]. UI after VVF closure was defined as any involuntary leakage of urine from the vagina that a patient complained about after obstetric VVF repair [ 11 ]. UI after successful obstetric VVF repair can include stress UI, overactive bladder, mixed UI, or bladder voiding disorder [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the highest successful closure of VVF repair, UI is a common and challenging public health problem among patients who underwent VVF repair [ 11 , 13 , 14 ]. Patients with UI experience wetness, odor, and discomfort [ 15 ], which have significant consequences for social and emotional problems such as relationship problems, depression, and suicidal ideation [ 16 ] and can affect women’s quality of life [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations